A QUALITATIVE OBSERVATION OF TEACHING AND LEARNING PROCESS ON ENGLISH LESSON AT WAHID HASYIM JUNIOR HIGH SCHOOL IN MALANG - LAILY, FITRIA NUR (Jurnal Ilmiah Mahasiswa FIB, 2015)
Teaching is a process that the teacher instructs the students to do something. While, learning is the acquisition of knowledge or skills through study, experience, or something being taught. In the teaching and learning process, the teacher and students do some activities in the classroom.  There are three kinds of activities in the classroom; opening, main and closing activities. Beside activities, there are also some students’ responses toward the English teacher in teaching and learning process. The study is aimed to describe the activities of English teaching and learning process and describe the students’ responses toward the English teacher in the teaching and learning process, especially in the Wahid Hasyim Junior High School Malang. This study shows that there are three activities in the English teaching and learning process; opening, main, and closing activities. Then, these are the students’ responses toward the English teacher; the students felt that the teacher was listened them, explained things clearly, helped them, trusted them, did not get angry quickly, etc.Keywords : Teaching, teacher, learning, learner.